2019
DOI: 10.1093/jxb/erz041
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew-associated microbes elicit defense responses against brown planthopper in rice

Abstract: The digestive waste product of sucking herbivores, known as honeydew, betrays the presence of brown planthopper to rice plants, due to the bacteria contained in the honeydew secretions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 97 publications
(122 reference statements)
2
39
0
Order By: Relevance
“…Through transient expression of 64 BPH salivary proteins in plants, six proteins were shown to elicit defense responses. Finally, bacteria in BPH honeydew were recently shown to activate rice defenses response in rice, including the accumulation of phytoalexins and the release of volatile compounds to attract natural enemies of BPH (Wari et al 2019). Together, these studies revealed that a variety of salivary proteins evoke defense responses in plant cells.…”
Section: Insect Elicitors and Effectorsmentioning
confidence: 98%
“…Through transient expression of 64 BPH salivary proteins in plants, six proteins were shown to elicit defense responses. Finally, bacteria in BPH honeydew were recently shown to activate rice defenses response in rice, including the accumulation of phytoalexins and the release of volatile compounds to attract natural enemies of BPH (Wari et al 2019). Together, these studies revealed that a variety of salivary proteins evoke defense responses in plant cells.…”
Section: Insect Elicitors and Effectorsmentioning
confidence: 98%
“…Considering more the association of this group of genes with human diseases, a related point to consider is that the CSP structure triggers plant immune responses when injected into the phloem, similarly to honeydew-associated microbes [77,78,79]. While CSP and/or honeydew microbes help release phytoalexins, jasmonic acid, salicylic acid and volatile organic compounds (VOCs) from the leaves, it would be interesting to see if the injection of CSP structures and/or the inoculation of specific bacteria such as A. baumannii, M./ S. caseolyticus, K. griseola and E. coli result in the activation of similar defense genes in the human tissue.…”
Section: Expression Of Chemosensory Protein (Csp) Structures In Pedicmentioning
confidence: 99%
“…Aside from the symbiotes inside the gut of BPH, BPH may ingest various microbes from rice plants and then secrete these microbes as honeydew. Interestingly, BPH honeydew strongly elicited the defense response of rice against BPH . The microbes from BPH honeydew induced the production of volatile organic compounds that attract natural enemies of BPH as well as the accumulation of phytoalexins in rice .…”
Section: Elicitors Promote Rice Defenses Against Planthoppersmentioning
confidence: 99%
“…Interestingly, BPH honeydew strongly elicited the defense response of rice against BPH . The microbes from BPH honeydew induced the production of volatile organic compounds that attract natural enemies of BPH as well as the accumulation of phytoalexins in rice . Such honeydew‐associated elicitors might have great potential for application in the control of planthoppers.…”
Section: Elicitors Promote Rice Defenses Against Planthoppersmentioning
confidence: 99%
See 1 more Smart Citation